Large linear non-saturating magnetoresistance and high mobility in ferromagnetic MnBi - He, Yangkun; Gayles, Jacob; Yao, Mengyu; Helm, Toni; Reimann, Tommy; Strocov, Vladimir N.; Schnelle, Walter; Nicklas, Michael; Sun, Yan; Fecher, Gerhard H.; Felser, Claudia (Nature Communications, 2021)
A large non-saturating magnetoresistance has been observed in several nonmagnetic topological Weyl semi-metals with high mobility of charge carriers at the Fermi energy. However, ferromagnetic systems rarely display a large magnetoresistance because of localized electrons in heavy d bands with a low Fermi velocity. Here, we report a large linear non-saturating magnetoresistance and high mobility in ferromagnetic MnBi. MnBi, unlike conventional ferromagnets, exhibits a large linear non-saturating magnetoresistance of 5000% under a pulsed field of 70 T. The electrons and holes’ mobilities are both 5000 cm2V−1s−1 at 2 K, which are one of the highest for ferromagnetic materials. These phenomena are due to the spin-polarised Bi 6p band’s sharp dispersion with a small effective mass. Our study provides an approach to achieve high mobility in ferromagnetic systems with a high Curie temperature, which is advantageous for topological spintronics.
CRIS-Team Scopus Importer:2022-04-14